Association of proton pump inhibitors with the occurrence of gut-derived bacteraemia in patients with haematological malignancy after chemotherapy. Issue 6 (2nd July 2016) - Zhou, Shu-Juan; Wang, Si-Qian; Ma, Yong-Yong; Tang, Li-Yuan; Shi, Yi-Fen; Liang, Bin; Chen, Yi; Yu, Kang
Abstract : Background : Gut-derived bacteraemia is a major complication in patients with haematological malignancy after chemotherapy. Objective : Our study aimed to investigate the role of proton pump inhibitors (PPIs) in the occurrence of gut-derived bacteraemia. Methods : We compared data from 92 hospitalized haematological malignancy patients after chemotherapy with gut-derived bacteraemia, collected from January 2009 to July 2015, with those of 92 contemporaneous, hospitalized haematological malignancy patients without bacteraemia. We evaluated PPIs use and analysed the effects of covariates. Results : Patients with gut-derived bacteraemia had a significantly higher incidence of PPIs use (69.6%) than that of controls (47.8%). Of the patients with gut-derived bacteraemia, only 44.6% had a documented indication for PPIs therapy. The antibacterial prophylaxis rate was 38.0% in the bacteraemia group and 58.7% in the non-antibacterial group. Based on multivariable logistic regression analysis, only PPIs use ( P  = 0.00, odds ratio (OR) = 0.546) was found to be associated with the risk of bacteraemia whereas antibacterial prophylaxis ( P  = 0.00, OR = 0.652) was protective. There were no significant differences in demographics, malignancy status, length of neutropenia, complications, or steroid use between the gut-derived bacteraemia and control group. Conclusions : This study suggests a potential association between PPIs use and development of gut-derived bacteraemia in haematological malignancy patients after chemotherapy.